3D Whole-Body MRI of the Musculoskeletal System - Pasoglou, Vassiliki; Van Nieuwenhove, Sandy; Peeters, Frank; Duchêne, Gaetan; Kirchgesner, Thomas; Lecouvet, Frederic E. (Seminars in Musculoskeletal Radiology, 2021)
With its outstanding soft tissue contrast, spatial resolution, and multiplanar capacities, magnetic resonance imaging (MRI) has become a widely used technique. Whole-body MRI (WB-MRI) has been introduced among diagnostic methods for the staging and follow-up assessment in oncologic patients, and international guidelines recommend its use. In nononcologic applications, WB-MRI is as a promising imaging tool in inflammatory diseases, such as seronegative arthritis and inflammatory myopathies. Technological advances have facilitated the introduction of three-dimensional (3D) almost isotropic sequences in MRI examinations covering the whole body. The possibility to reformat 3D images in any plane with equal or almost equal resolution offers comprehensive understanding of the anatomy, easier disease detection and characterization, and finally contributes to correct treatment planning. This article illustrates the basic principles, advantages, and limitations of the 3D approach in WB-MRI examinations and provides a short review of the literature.
Keywords: whole-body MRI; three-dimensional; oncologic imaging; rheumatologic imaging; musculoskeletal Imaging